Shatter and splatter: The contribution of mechanical and optical properties to the perception of soft and hard breaking materials - Schmid, Alexandra C.; Doerschner, Katja; Justus Liebig University Giessen (My University, 2018)
Abstract Research on the visual perception of materials has mostly focused on the surface qualities of rigid objects. The perception of substance like materials is less explored. Here, we investigated the contribution of, and interaction between, surface optics and mechanical properties to the perception of nonrigid, breaking materials. We created novel animations of materials ranging from soft to hard bodies that broke apart differently when dropped. In Experiment 1, animations were rendered as point-light movies varying in dot density, as well as ´full-cue´ optical versions ranging from translucent glossy to opaque matte under a natural illumination field. Observers used a scale to rate each substance on different attributes. In Experiment 2 we investigated how much shape contributed to ratings of the full-cue stimuli in Experiment 1, by comparing ratings when observers were shown movies versus one frame of the animation. The results showed that optical and mechanical properties had an interactive effect on ratings of several material attributes. We also found that motion and static cues each provided a lot of information about the material qualities; however, when combined, they influenced observers´ ratings interactively. For example, in some conditions, motion dominated over optical information; in other conditions, it enhanced the effect of optics. Our results suggest that rating multiple attributes is an effective way to measure underlying perceptual differences between nonrigid breaking materials, and this study is the first to our knowledge to show interactions between optical and mechanical properties in a task involving judgments of perceptual qualities.
Keywords: ddc:150